A correlation analysis of HHV infection and its predictive factors in an HIV‐seropositive population in Yunnan, China. Issue 3 (18th November 2019) - Ren, Li; Wang, Binghui; Miao, Zhijiang; Liu, Pan; Zhou, Shiyi; Feng, Yun; Yang, Shuting; Xia, Xueshan; Wang, Kunhua
Abstract: Human herpesviruses (HHVs) have a particularly high prevalence in certain high‐risk populations and cause increased morbidity and mortality in patients with acquired immunodeficiency syndrome (AIDS). Screening and treating subclinical HHV infections reduce human immunodeficiency virus (HIV) infection incidence, disease progression, and transmission. However, there are few studies on HHVs, HIV coinfection rates, and their related risk factors. We aimed to clarify the prevalence of all eight HHVs in peripheral blood samples collected from HIV‐positive patients, and explore the association of HHV infection in HIV‐positive patients in an HIV‐seropositive population in Yunnan. We recruited 121 HIV‐positive patients with highly active antiretroviral therapy (HAART) and 45 healthy individuals. All the eight HHVs were detected using polymerase chain reaction and their epidemiological information and clinical data were collected and statistically analyzed. A high prevalence of HHVs (89.3%) was observed in individuals with HIV infections and with herpes simplex virus (HSV)‐2 (65.3%), and HSV‐1 (59.5%) being the most common. Coinfection with more than two different HHVs was more common in patients with HIV infections receiving HAART (72.7%) than in healthy controls. Older age, being married, higher HIV‐1 plasma viral loads, and use of antiviral protease inhibitors were independently correlated with an increased frequency of HHVs, but we found no association with CD4 count, WHO HIV clinical stage, and HIV infection duration. Our findings are of great significance for the prevention of HHV opportunistic infection in patients with AIDS and their clinical treatment. Highlight: HHV co‐infection in AIDS patients deserves attention during the course of antiviral therapy. Suppressing HHV recurrences had a clinically significant effect on prolonging survival in some cohorts of HIV‐infected patients and may be an effective intervention in reducing HIV spread in China.